Electrical Characterization of ZnO Nano Composites - Gangopadhyay, Arnab; Sarkar, Aditi; Sarkar, A. (Asian Journal of Chemistry, 2011)
In this work ZnO nano clusters were grown in biopolymer, gum acacia background. Attempt has made to control the nano-cluster size by in situ chemical sol-gel process through the control of the rate of forward reaction. X-Ray diffraction study and optical absorption study and D.C. conductivity study on the nano clustered material were done to get information on grain size. An empirical formula relating nano-size and conductivity fluctuation has been proposed here on the basis of preliminary observation. The work indicates a possible new characterization technique by the use of the D.C. I-V characteristics. Results of electrical transport through the developed nano-composites are found to exhibit dominant quantum effect at room temperature.